2016
DOI: 10.1016/j.cub.2016.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Mice Develop Efficient Strategies for Foraging and Navigation Using Complex Natural Stimuli

Abstract: SUMMARY The ability to shift between multiple decision-making strategies during natural behavior allows animals to strike a balance between flexibility and efficiency. We investigated odor-guided navigation by mice to understand how decision making strategies are balanced during a complex natural behavior. Mice navigated to odor sources in an open arena using naturally fluctuating airborne odor cues as their positions were recorded precisely in real time. When mice had limited prior experience of source locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 45 publications
3
104
1
Order By: Relevance
“…Desert ants, Cataglyphis fortis, have been shown to use learned olfactory scenes for homeward navigation in the absence of other directional cues [58]. Similarly, in mice, efficient foraging strategies can overtake an otherwise local gradient ascent strategy, if prior information about the odor scene is available [59]. It is possible that the stochastic random walk strategies we observe here could be replaced with more stereotyped maneuvers if flies were sufficiently preconditioned to the environment.…”
Section: Discussionmentioning
confidence: 76%
“…Desert ants, Cataglyphis fortis, have been shown to use learned olfactory scenes for homeward navigation in the absence of other directional cues [58]. Similarly, in mice, efficient foraging strategies can overtake an otherwise local gradient ascent strategy, if prior information about the odor scene is available [59]. It is possible that the stochastic random walk strategies we observe here could be replaced with more stereotyped maneuvers if flies were sufficiently preconditioned to the environment.…”
Section: Discussionmentioning
confidence: 76%
“…Next, organization of exploratory behavior was not observed to differ between control and olfactory bulbectomized rats [58]. Nevertheless, a recent study demonstrated that mice readily use any available cues, including airborne odor plumes, when navigating within a novel environment [59]. However, the present study was conducted within a closed chamber with little or no air movement, thus limiting the availability of airborne odors.…”
Section: Discussionmentioning
confidence: 94%
“…In Box 1, we describe parallels between the responses of single cells to chemical gradients, and the responses of single animals and animal groups to environmental gradients. The important point is that the use of spatial gradients is a fundamental part of the search strategies of cells like neutrophils (16) and bacteria (17), solitary animals like mice and fruit flies (18,19), and large animal groups like fish schools (20). In all cases, the searching individual or group has a means of measuring a signal differential (e.g., difference in signal strength or the timing of signal arrival between sensors) over space, and responding to that differential by altering locomotory behavior in a way that causes the individual or group to climb the gradient ( Fig.…”
Section: The Evolution Of Search Strategiesmentioning
confidence: 99%
“…In well-studied microorganisms, such as Escherichia coli, the biochemical pathways involved in decision-making are understood thoroughly enough that models of gradient-climbing can be formulated directly from the knowledge of intracellular signaling pathways that govern the gradient response (23)(24)(25). In the case of animals, the neural processes involved in integrating and making decisions using measurements of a gradient are not as well understood; however, the key features of the signal integration and decisionmaking process can be inferred using experiments that provide known sensory input and map this input to observed searcher motions (18,20,26). In this way, researchers are beginning to understand how measurements of spatial gradients lead to gradient-climbing behavior in a wide variety of model systems.…”
Section: The Evolution Of Search Strategiesmentioning
confidence: 99%
See 1 more Smart Citation